Integrity of the alveolar-capillary barrier and alveolar surfactant system in smokers. Issue 8 (August 1992) - Schmekel, B; Bos, J A; Khan, A R; Wohlfart, B; Lachmann, B; Wollmer, P
Abstract : BACKGROUND: The permeability of the alveolar-capillary barrier to technetium-99m labelled diethylenetriamine pentaacetate (99mTc DTPA) is known to be greatly increased in smokers, but the underlying mechanism is poorly understood. Abnormal permeability of the alveolar epithelium as well as impaired surfactant function has been suggested. The purpose of this study was to examine transudation of urea and albumin into the alveoli and alveolar surfactant function in smokers and non-smokers and to relate these variables to the rate of alveolar-capillary transfer of 99mTc DTPA. METHODS: Standardised bronchoalveolar lavage was performed and the yield of urea and albumin measured in the lavage fluid. The integrity of the alveolar surfactant system was assessed by measurement of the surface activity and of the yield of phospholipids in alveolar lavage fluid. RESULTS: The mean decay constant for the pulmonary clearance of 99mTc DTPA was 0.028/min in the smokers and 0.009/min in the non-smokers. The recovery of albumin and urea in alveolar lavage fluid was very similar in the two groups. The surface activity of alveolar lavage fluid was lower in smokers than in non-smokers (minimum surface tension 37.9 versus 28.6 mN/m) and the yield of phospholipids was reduced (2.08 versus 3.86 mg). The rate constant for the pulmonary clearance of 99mTc DTPA correlated with the yield of phospholipids at bronchoalveolar lavage. CONCLUSIONS: The study shows that increased alveolar-capillary transfer of 99mTc DTPA in smokers is not accompanied by increased transudation of small or large molecules into the alveoli. The findings support the hypothesis that increased clearance of 99mTc DTPA in smokers is related to surfactant dysfunction.